ANALYSIS OF THE CO2 VERTICAL PROFILE OF IN A FOREST AREA IN THE CENTRAL AMAZON - Silva, Mylena Vieira (2015)
http://dx.doi.org/10.5902/2179460X16210This study aimed to describe the vertical profile of CO2 concentration during least rainy period and rainy periods of 2006 , into an area of tropical forest in the Central Amazon, Brazil . It were used data of CO2, collected at various heights by a system of measures including an infrared gas analyzer (Licor 7000), in a tower with 40 meters of height. From the data collected it was observed that the concentration of CO2 decreases as one moves from the ground to the top of the canopy. This suggests that the largest source of CO2 is from the soil, due to processes such as respiration and decomposition of plant biomass. When is compared the least rainy and the most rainy periods, it is noted significant differences in the amounts of CO2 concentration in these periods. The highest concentrations were observed during least rainy period, with monthly mean values above 440 ppm near the surface.